PERAN KUALITAS KEMELEKATAN ANAK TERHADAP PERILAKU SOSIAL - Fauziah Nasution (JURNAL RAUDHAH, 2016)
attachment is a relationship between two people who have emotional ties that last a long time caused one to feel comfort, pleasure and confidence in other, and it can form attachment behavior. Every baby has experience different attachment so you can find patterns of attachment, namely: secure attachment, attachment avoidance, resistance and clinging attachment disorganization.  The development of attachment to the baby began to rise in the first half, the quality of which is owned by infant attachment may affect social behavior in the future.  With a secure attachment baby will be able to interact socially with good, do not get frustrated, have achievements, and the development of the whole of their competence, as well as the management of true emotions